The Collapse of Donkey’s Ear Abalone (Haliotis asinina) Fishery in Siquijor, Philippines - Wagey, Billy Theodrus (e-Journal BUDIDAYA PERAIRAN, 2014)
We briefly describe the localized abalone (Haliotis asinina) fishery in Siquijor Island, central Philippines and discussed the possible reasons of the sudden collapse in local trade and fishery. The lack of management system may have contributed to over-exploitation of abalone leading to closure in 2012. Prior to the collapse in 2012, abalone gatherers spent an average of 4.18±0.15 hours/day/site with catch-per-unit-effort (CPUE) of H. asinina ranged from 0.1 to 0.6 kg/person/hr with mean value of 0.25±0.03 (SE) kg/person/hr. Recommendations to revive and sustain the abalone fishery of Siquijor Island are also provided.   Keywords: abalone, fishery, overharvesting, Siquijor